Global Inequality of Opportunity : How Much of Our Income Is Determined By Where We Live? - Milanovic, Branko (MIT Press, 2015)
Suppose that all people in the world are allocated only two characteristics over which they have (almost) no control: country of residence and income distribution within that country. Assume further that there is no migration. We show that more than one-half of variability in income of world population classified according to their household per capita in one-percent income groups (by country) is accounted for by these two characteristics. The role of effort or luck cannot play a large role in explaining global distribution of income.